Importancia de los microorganismos en suelos cultivados con palma aceitera (Elaeis guineensis Jacq) en el Ecuador - Aviles Lindao, Ginger Julexi (2022)
Oil palm (Elaeis guineensis Jacq) is a crop that produces the largest amount of oil in the world, which is consumed by more than 70% of the world's population. With a production cycle of 25 to 30 years, it grows below 500 meters above sea level, although it thrives in humid areas, although it develops well in swampy regions. The roots of oil palm plants are a suitable habitat for the development of microorganisms connected to the roots of plants. The interaction of soil microorganisms with plant roots meets the basic nutritional needs of plants and their associated microbial communities. The beneficial effects of arbuscular mycorrhizae in the soil are closely related to their effects on plants, as these (soil – plant) are closely related. However, it can be stated that mycorrhizae perform multiple functions in the soil, greatly improving the potential for agricultural production, their possibilities of supporting and maintaining a wide variety of plant species. Some of the benefits offered by Rhizobium include: disease-free plants, higher agricultural yields, lower production costs due to lower fertilizer consumption, and environmental quality. The effect of the use of Trichoderma in oil palm (Elaeis guineensis Jacq) is a good example of the response in a crop that has had recurrent problems in agronomic management due to the poor development of its roots due to biotic and abiotic causes.